Análise da percepção da qualidade dos serviços educacionais em uma instituição de ensino pública federal: um modelo para avaliação institucional na educação profissional técnica de nível médio - Ribeiro, Ricardo Luís Alves de Oliveira (2024)
This dissertation analyzes the perception of the quality of educational services in a federal public educational institution, proposing a model for institutional evaluation in Technical and Vocational Education and Training. The work was developed within the scope of the Graduate Program in Vocational and Technological Education (ProfEPT) at the Federal Institute of Alagoas (IFAL), Benedito Bentes Campus. The research adopted a quantitative approach, using questionnaires based on the HEDPERF and SINAES models to collect data from students of technical courses. The model was tested and applied at IFAL - Satuba Campus in the medium-level integrated technical courses in Agroindustry and Agriculture. The results indicate that the quality dimensions most valued by students are Reputation, Access, Academic Aspects, and Academic and Professional Training. Statistical analysis confirmed the adequacy and validity of the proposed model, which can be used as an educational product for the continuous improvement of services offered by Federal Institutes. As a second educational product, a guide for using the model was developed. The originality of the work lies in the adaptation of quality evaluation models to the specific context of vocational and technological education, providing a robust tool for educational management.